Pre‐ischemia melatonin treatment alleviated acute neuronal injury after ischemic stroke by inhibiting endoplasmic reticulum stress‐dependent autophagy via PERK and IRE1 signalings. Issue 3 (6th March 2017) - Feng, Dayun; Wang, Bao; Wang, Lei; Abraham, Neeta; Tao, Kai; Huang, Lu; Shi, Wei; Dong, Yushu; Qu, Yan
Abstract: Melatonin has demonstrated a potential protective effect in central nervous system. Thus, it is interesting to determine whether pre‐ischemia melatonin administration could protect against cerebral ischemia/reperfusion (IR)‐related injury and the underlying molecular mechanisms. In this study, we revealed that IR injury significantly activated endoplasmic reticulum (ER) stress and autophagy in a middle cerebral artery occlusion mouse model. Pre‐ischemia melatonin treatment was able to attenuate IR‐induced ER stress and autophagy. In addition, with tandem RFP‐GFP‐LC3 adeno‐associated virus, we demonstrated pre‐ischemic melatonin significantly alleviated IR‐induced autophagic flux. Furthermore, we showed that IR induced neuronal apoptosis through ER stress related signalings. Moreover, IR‐induced autophagy was significantly blocked by ER stress inhibitor (4‐PBA), as well as ER‐related signaling inhibitors (PERK inhibitor, GSK; IRE1 inhibitor, 3, 5‐dibromosalicylaldehyde). Finally, we revealed that melatonin significantly alleviated cerebral infarction, brain edema, neuronal apoptosis, and neurological deficiency, which were remarkably abolished by tunicamycin (ER stress activator) and rapamycin (autophagy activator), respectively. In summary, our study provides strong evidence that pre‐ischemia melatonin administration significantly protects against cerebral IR injury through inhibiting ER stress‐dependent autophagy. Our findings shed light on the novel preventive and therapeutic strategy of daily administration of melatonin, especially among the population with high risk of cerebral ischemic stroke.